2004
DOI: 10.1163/1568540043165985
|View full text |Cite
|
Sign up to set email alerts
|

Reported Siphonostomatoid Copepods Parasitic on Marine Fishes of Southern Africa

Abstract: Worldwide there are more than 12000 species of copepods known, of which 4224 are symbiotic. Most of the symbiotic species belong to two orders, Poecilostomatoida (1771 species) and Siphonostomatoida (1840 species). The order Siphonostomatoida currently consists of 40 families that are mostly marine and infect invertebrates as well as vertebrates. In a report on the status of the marine biodiversity of South Africa, parasitic invertebrates were highlighted as taxa about which very little is known. A list was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…In 2005, Dippenaar performed a detailed literature search, focusing on South Africa only, and compiled an updated list of the marine parasitic copepods, including the hosts known as well as the localities within South Africa (Dippenaar 2005). At that stage, only 9% of the world's siphonostomatoids were reported from southern African waters indicating the necessity for increased investigations into this parasitic group.…”
Section: Copepodamentioning
confidence: 99%
“…In 2005, Dippenaar performed a detailed literature search, focusing on South Africa only, and compiled an updated list of the marine parasitic copepods, including the hosts known as well as the localities within South Africa (Dippenaar 2005). At that stage, only 9% of the world's siphonostomatoids were reported from southern African waters indicating the necessity for increased investigations into this parasitic group.…”
Section: Copepodamentioning
confidence: 99%
“…Echthrogaleus denticulatus has been reported from the pelagic thresher sharks of the Southern Africa (Dippenaar 2004), Thailand's EEZ of Andaman sea (Watchariya et al 2009) and North-eastern Brazil (Santander-neto & Lessa 2013) and from the west coast of India (Pillai 1985). Asok Kumar (1990) reported the presence of E. denticulatus from Eulamia dussumeri and E. ellioti from Kerala coast, along southwest coast of India.…”
Section: Discussionmentioning
confidence: 99%
“…E. denticulatus has a wide distribution, having been reported from at least nine different shark species, in the Atlantic, Pacific and Indian Oceans (Cressey 1967;Hewitt 1979;Izawa 2010;Oldewage & Smale 1993;Pilla 1985;Shiino 1954;Smith 1874;Watchariya et al 2009). E. denticulatus was reported on A. pelagicus from the Indian Ocean (Madagascar coast), South African coast, north-eastern Brazil, Thailand and Oman waters (Cressey 1867;Dippenaar 2004;Henderson et al 2013;Santander-Neto & Lessa 2013;Watchariya et al 2009). Hence, this study on the occurrence of E. denticualtus as an ectoparasite on Alopias pelagicus from the Indian EEZ of Andaman Sea provides a new distribution record for the species.…”
Section: Introductionmentioning
confidence: 99%
“…Although 429 species, representing 12 of the 39 known families, have been reported from South Africa, all of these infect fish (Dippenaar 2004). Prior to this study, none of the 12 families reported to infect invertebrate hosts had been recorded from South Africa (Dippenaar 2016).…”
Section: Introductionmentioning
confidence: 92%